A method for testing surface roughness change rate of a heterojunction cell and a method for replenishing liquid in a CP tank
Patent Information
- Application Number
- CN202211296625.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-21
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-10-21
AI Technical Summary
[0005]在实际生产过程中,随着生产批次的增加,CP溶液中的HF和HCl会逐渐消耗,其浓度不断发生变化,药液稳定性较差,药液寿命逐渐变低,这些因素都会影响绒面金字塔的修饰效果,CP溶液配比的稳定性是控制绒面金字塔表面粗糙度变化率稳定的关键
本发明根据表面粗糙度变化率值的反馈进行药液补加,使药液浓度在稳定范围内,从而使金字塔表面粗糙度变化率在预定范围内,达到了对药液浓度精准控制的目的,提高了药液批次间的稳定性,使绒面金字塔表面粗糙度变化率稳定性得到控制,整体的非晶硅薄膜沉积质量更佳,电池的效率、良率、钝化效果更好。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of textured pyramid-shaped heterojunction solar cells, and in particular to a method for testing the surface roughness change rate of heterojunction solar cells and a method for replenishing CP tank using the surface roughness change rate of heterojunction solar cells. Background Technology
[0002] The main process for preparing silicon-based heterojunction solar cells (HJT) is as follows: a (100) crystal orientation monocrystalline silicon wafer is used as a substrate for cleaning and texturing, amorphous silicon thin films are deposited on both sides, transparent conductive oxide thin films are deposited on both sides, and metal electrodes are prepared by screen printing to form an HJT solar cell with a symmetrical structure.
[0003] Typically, a mixed solution of alkali and additives is used to anisotropically etch a (100) oriented monocrystalline silicon wafer, forming a "pyramid-like" textured surface to increase the absorption of incident light. A nanometer-thick hydrogenated intrinsic amorphous silicon film (ia:Si:H) is then grown on the textured surface using PECVD deposition to passivate the surface. The pyramids formed naturally by alkali etching often have sharp, uneven apex, edges, and base valleys. The amorphous silicon passivation film deposited at these sharp points and edges is of relatively poor quality, affecting the passivation effect.
[0004] To address this, a chemical polishing (CP) solution, a mixture of hydrofluoric acid (HF) and hydrochloric acid (HCl) with ozone (O3), is typically used to round the textured pyramids. The principle behind CP etching of the textured pyramids is as follows: high-concentration ozone oxidizes silicon to silicon oxide, and HF then isotropically etches, polishes, and grinds the resulting silicon oxide, resulting in a smoother texture. The hydrogenated amorphous silicon film (ia:Si:H) deposited on the textured surface after CP exhibits better quality and a more significant passivation effect.
[0005] In actual production, as the number of production batches increases, HF and HCl in the CP solution will be gradually consumed, their concentrations will change continuously, the stability of the solution will be poor, and the solution life will gradually decrease. These factors will affect the modification effect of the suede pyramid. The stability of the CP solution ratio is the key to controlling the stability of the surface roughness change rate of the suede pyramid.
[0006] Currently, the replenishment of CP solution in the CP bath generally relies on the production experience of technicians to control the concentration of the CP solution. This leads to inaccurate control of the CP solution concentration, inconsistent pyramid sphericity, and production line fluctuations. Insufficient HF replenishment will not achieve the required etching rate, resulting in insufficient change in the pyramid surface roughness, affecting the deposition quality of the amorphous silicon thin film, reducing minority carrier lifetime, and decreasing cell efficiency. Excessive HF replenishment will damage the pyramid structure, increase reflectivity, similarly reducing cell efficiency, and also increasing fluoride ion emissions, thus increasing production costs. Improper HCl replenishment will cause unstable pH values in the CP solution, leading to unstable ozone concentrations, affecting sphericity, causing production line fluctuations, and ultimately reducing yield.
[0007] Therefore, controlling the stability of the roundness of the textured pyramid is key to improving the stability of the HJT battery production process, as well as the battery yield and efficiency. Summary of the Invention
[0008] The technical problem to be solved by this invention is to provide a method for testing the surface roughness change rate of heterojunction solar cells and a method for replenishing CP solution in the CP cell using the surface roughness change rate of heterojunction solar cells. By measuring the surface roughness of the textured surface of different batches of solar cells after texturing, a quantitative parameter Y value characterizing the surface roughness change rate of the pyramid is calculated. Then, by monitoring the surface roughness change rate Y value of the pyramid, the CP solution is quantitatively replenished, thereby accurately controlling the solution concentration, maintaining the stability of the solution between batches, keeping the surface roughness change rate of the pyramid stable, improving the deposition quality of intrinsic amorphous silicon thin films (ia:Si:H) and the efficiency and yield of the cells.
[0009] To solve the above-mentioned technical problems, the technical solution of the present invention is as follows: A method for testing the surface roughness change rate of a heterojunction solar cell includes the following steps: S1. The silicon wafer is texturized in a cleaning tank. The surface of the silicon wafer after texturing forms a pyramid-shaped textured surface. The surface roughness R0 of the pyramid-shaped textured surface is measured. S2. Place the texturized silicon wafer in a CP bath containing CP solution. The CP solution rounds the pyramid-shaped textured surface, and the surface roughness R1 of the rounded pyramid-shaped textured surface is measured. S3. Calculate the surface roughness change rate Y1 of the pyramid-shaped textured surface using the surface roughness change rate formula. The surface roughness change rate formula is: Y1=(R0-R1) / R0; S4. Repeat steps S1 to S3 to obtain a series of surface roughness change rates.
[0010] Furthermore, in step S2, the concentration of HF in the CP solution is 2-10%, the concentration of HCl is 0.5%-15%, and the concentration of ozone is 30-50 ppm.
[0011] Furthermore, the device used to measure the surface roughness of the pyramid-shaped textured surface is a confocal microscope.
[0012] A method for replenishing CP tank using the surface roughness change rate of heterojunction solar cells includes the following steps: Step a. Pass multiple batches of silicon wafers through the same cleaning tank and CP tank in sequence. Each batch of silicon wafers includes multiple silicon wafers. Select n silicon wafers and use the test method to test the surface roughness change rate of the silicon wafers. Calculate the average surface roughness change rate Y' of the n silicon wafers. If the average Y' is within 8~12%, do not replenish the CP tank. If the average Y' is not within 8~12%, replenish the CP tank.
[0013] Furthermore, step b is included after step a: Multiple batches of silicon wafers are continuously passed through the same cleaning tank and CP tank in sequence until the average value of the surface roughness change rate Y” of the selected silicon wafers is not between 8 and 12%. Assuming that the silicon wafer with the average value Y” not between 8 and 12% is in the nth batch, the adjacent previous batch is the n-1th batch, and the replenishment volume of the CP tank between the n-1th batch and the nth batch is m1, then according to step a, it is determined whether the average value of the surface roughness change rate of the silicon wafer obtained by testing and calculation is within 8 to 12%.
[0014] Furthermore, when the average surface roughness change rate of the silicon wafer is within 8~12%, step a is repeated multiple times to conduct a stability verification test of the replenishment amount m1. When the average surface roughness change rate of the silicon wafer is still within 8~12%, the replenishment amount of the CP tank between the (n-1)th batch and the nth batch is m1. At the same time, the average surface roughness change rate of the silicon wafer in the (n+1)th batch after the nth batch is tested.
[0015] Furthermore, the concentration of HF in the CP solution in the CP tank is 2-10%, the concentration of HCl is 0.5-15%, and the concentration of ozone is 30-50 ppm.
[0016] Furthermore, when the average value of the surface roughness change rate of the silicon wafer is not within 8~12%, the replenishment volume of the CP tank is reset to m2, and then, according to step a, it is determined whether the average value of the surface roughness change rate of the silicon wafer obtained by testing and calculation is within 8~12%.
[0017] The surface roughness R0 of the suede before CP cleaning was tested. An initial CP solution was prepared with HF concentration of 2%-10%, HCl concentration of 0.5%-15%, and ozone concentration of 30-50 ppm. The first reaction was carried out at 15℃ for 180 seconds. After the reaction, the surface roughness R0 of the suede after CP cleaning was tested. 1 Using the formula Y=(R0-R) / R0, the roundness value of the first batch of textured pyramids after the initial CP tank preparation is between 8% and 20%. The second batch of reaction continues, and the surface roughness of the pyramids after the second CP is tested on silicon wafers to obtain the surface roughness change rate of the second batch of pyramids.
[0018] If the surface roughness change rate of the second batch of pyramids is within 8%-20%, no additional reagent needs to be added, and the next batch of reaction can proceed. If it is outside the predetermined range, the reagent needs to be added, and the surface roughness change rate value should be tested again after the reaction.
[0019] Compared with the prior art, the present invention has the following beneficial effects: This invention replenishes the chemical solution based on feedback from the surface roughness change rate, keeping the chemical solution concentration within a stable range. This, in turn, keeps the surface roughness change rate of the pyramid within a predetermined range, achieving precise control of the chemical solution concentration. This improves the stability between batches of chemical solutions, controls the stability of the surface roughness change rate of the textured pyramid, and results in better overall amorphous silicon thin film deposition quality, leading to better battery efficiency, yield, and passivation effect. Detailed Implementation
[0020] The present invention will now be described in detail with reference to specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention, but are not intended to limit the present invention.
[0021] Example 1: Test method for surface roughness change rate of heterojunction solar cells HJT batteries typically use a high-concentration ozone solution (a mixture of HF, HCl, and O3) to polish and round the textured pyramid morphology. The general process involves using N-type monocrystalline silicon as a substrate, polishing and texturing it to form a pyramid textured surface with a good light-trapping structure, and then polishing and rounding the pyramid. To overcome the technical problem of unstable surface roughness change rate of the pyramid morphology caused by inaccurate electrolyte replenishment in existing technologies, which affects the passivation effect of amorphous silicon thin films, this method uses the surface roughness change rate value of the textured pyramid to precisely control the electrolyte concentration.
[0022] Using N-type silicon wafers, polishing, cleaning, and texturing were completed. The silicon wafer thickness was 140 μm. A CP solution with an initial concentration of 3.57% HF, 4.28% HCl (HF:HCl = 1:1.2), and 50 ppm ozone was prepared. The surface roughness change rate of different batteries was obtained. The surface roughness change rate test method included the following steps: S1. A silicon wafer with a thickness of 140μm is texturized in a cleaning tank. The surface of the silicon wafer after texturing forms a pyramid-shaped textured surface. The surface roughness R0 of the pyramid-shaped textured surface is measured using a confocal microscope. S2. Place the texturized silicon wafer in a CP bath containing CP solution. The CP solution rounds the pyramid-shaped textured surface, and the surface roughness R1 of the rounded pyramid-shaped textured surface is measured. S3. Calculate the surface roughness change rate Y1 of the pyramid-shaped textured surface using the surface roughness change rate formula. The surface roughness change rate value is quantitatively characterized by the percentage reduction in surface roughness relative to the unrounded surface roughness. That is, the surface roughness change rate formula is: Y1=(R0-R1) / R0. S4. Repeat steps S1 to S3 to obtain a series of surface roughness change rates.
[0023] The battery fabrication was completed using existing technology, and the minority carrier lifetime of different batteries was measured. The test results are shown in Table 1.
[0024] Table 1 shows that different surface roughness change rates correspond to different minority carrier lifetimes. When the surface roughness change rate is between 8% and 20%, the minority carrier lifetime is around 3000 μs. However, when the surface roughness change rate is less than 8% or greater than 20%, the minority carrier lifetime decreases significantly. Therefore, this invention sets the surface roughness change rate range for determining whether to replenish the fluid to 8-20%. Minority carrier lifetime is a quantitative indicator of passivation effect; a higher minority carrier lifetime indicates a better passivation effect.
[0025] Example 2: A method for replenishing CP tank using the surface roughness change rate of heterojunction solar cells. Typically, texturing equipment is silicon wafer cleaning equipment, which includes multiple cleaning tanks arranged in parallel. Depending on the process requirements, each cleaning tank is filled with chemical solution or pure water. It also includes at least one CP tank, which is filled with CP solution. Silicon wafers (usually multiple silicon wafers are carried in a carrier) pass through multiple cleaning tanks to complete the texturing of the silicon wafers.
[0026] The method for replenishing the CP tank using the surface roughness change rate of heterojunction solar cells includes the following steps: Step a. Pass multiple batches of silicon wafers through the same cleaning tank and CP tank in sequence. Each batch of silicon wafers includes multiple silicon wafers. Select n silicon wafers and test the surface roughness change rate of the silicon wafers using the test method in Example 1. Calculate the average surface roughness change rate Y' of the n silicon wafers (as shown in Table 1). If the average Y' is within 8~12%, do not replenish the CP tank. If the average Y' is not within 8~12%, replenish the CP tank.
[0027] Step b. Continuously pass multiple batches of silicon wafers through the same cleaning tank and CP tank in sequence until the average surface roughness change rate Y” of the selected silicon wafers is not between 8 and 12%. Assume that the silicon wafer with the average Y” not between 8 and 12% is in the nth batch, the adjacent previous batch is the n-1th batch, and the replenishment volume of the CP tank between the n-1th batch and the nth batch is m1. Then, according to step a, determine whether the average surface roughness change rate of the silicon wafer obtained by testing and calculation is within 8 to 12%.
[0028] When the average surface roughness change rate of the silicon wafer is within 8~12%, repeat step a multiple times to conduct a stability verification test of the replenishment amount m1. When the average surface roughness change rate of the silicon wafer is still within 8~12%, the replenishment amount of the CP tank between the (n-1)th batch and the nth batch is m1. Then continue to test the average surface roughness change rate of the silicon wafers in the (n+1)th batch after the nth batch.
[0029] When the average surface roughness change rate of the silicon wafer is not within 8-12%, the replenishment volume of the CP bath is reset to m2, and then, according to step a, the average surface roughness change rate of the silicon wafer obtained from testing and calculation is again determined to be within 8-12%. The reaction time for each rounding reaction is 180 seconds, and the reaction temperature is 15℃. The replenishment volume between batches is determined based on the surface roughness change rate value, controlling the fluctuation range of the surface roughness change rate to within 1%-2%. Specifically: N-type silicon wafers were used for polishing, cleaning, and texturing; the wafer thickness was 140μm. A CP solution was initially prepared with an HF concentration of 3.57%, an HCl concentration of 4.28%, and an ozone concentration of 50 ppm. A batch of 400 silicon wafers (100 wafers per carrier, with four carriers simultaneously entering and exiting a cleaning tank or CP tank) is defined, and the surface roughness change rate of multiple silicon wafers in each batch is detected sequentially.
[0030]
[0031] Table 2 shows the average surface roughness change rates of multiple batches of silicon wafers, including the first batch (Y1), the second batch (Y2), and the third batch (Y3). These average surface roughness change rates are then compared to the range of 8-20%. No additional solution is needed when the average surface roughness change rate is within 8-20%, while an appropriate amount of solution needs to be added when the change rate is less than 8%.
[0032] After replenishment, repeat the same surface roughness change rate test under the same solution and equipment parameters. Compare the average surface roughness change rate with the range value, and then repeat the test until the average surface roughness change rate is within 8-20%. If the first batch of tests does not show any non-compliant surface roughness change rate values, continue testing with multiple batches until the silicon wafer surface roughness change rate fails to meet requirements. Based on this, test the replenishment amount.
[0033] The amount of fluid replenishment between each batch is shown in Table 3:
[0034] Liquid replenishment volume 1 is the liquid replenishment volume between the first batch and the second batch, liquid replenishment volume 2 is the liquid replenishment volume between the second batch and the third batch, and so on. Let's assume that the first batch where the average surface roughness change rate does not meet the requirements is batch n. Then, set the liquid replenishment volume between batch n and batch n-1 as m1. Repeat the original test group (i.e., test one), keeping the test conditions before batch n-1 unchanged. After batch n-1, add liquid replenishment volume m1 and test whether the average surface roughness change rate is within the range. If it is, it meets the range requirements. Repeat test one multiple times for verification test to test the stability of liquid replenishment volume m1. If there is no change, continue to complete the surface roughness change rate test for batch n+1 based on test one. If the same batch with the surface roughness change rate does not meet the requirements, refer to the liquid replenishment method for batch n. If the requirements are not met, repeat the original test group (Test 2), keeping the test conditions unchanged until batch n-1. After batch n-1, add a replenishment volume m2 and test whether the average surface roughness change rate is within the range. If it is within the range, repeat Test 2 multiple times for verification testing to test the stability of the replenishment volume m2. If there is no change, continue to complete the surface roughness change rate test for batch n+1 based on Test 2. If batches with surface roughness change rates that do not meet the requirements also appear, refer to the replenishment method for batch n. If the requirements are not met, repeat the original test group (Test 3)... and repeat the above steps until a suitable m value is found that keeps the surface roughness change rate within the range.
[0035] Verification test: After n batches of the original test group have failed to meet the required range of surface roughness change rate, the liquid volume is directly added, and then the surface roughness change rate is tested again for verification. If the measured surface roughness change rate meets the required range of surface roughness change rate, the verification is repeated by increasing or decreasing the amount.
[0036] Using the methods described above, the replenishment volume for each of the n batches was finally determined, as shown in Table 4: m n This indicates the amount of fluid replenishment between batch n and batch n+1.
[0037] Application examples There are various processes for fabricating solar cells, such as heterojunction, Topcon, and PERC cells. Cleaning and texturing are necessary steps in making cells from silicon wafers. Therefore, taking the heterojunction cell fabrication process as an example, this paper illustrates that a liquid replenishment system established by the surface roughness change rate Y can obtain a textured pyramid with a stable surface roughness change rate. Tests show that the average efficiency of cells fabricated using this method is improved by 0.1-0.2%.
[0038] The main fabrication process of heterojunction solar cells is as follows: cleaning and texturing → PEVCD coating → PVD coating → screen printing.
[0039] Experiment 1: With a determined replenishment volume (as shown in Figure 4), the chemical solution was replenished in batches to complete the cleaning and texturing of the silicon wafers and subsequent process flow, and the efficiency of the battery was measured.
[0040] Experiment 2: In determining the replenishment amount, the replenishment amount in the previous experiment before the surface roughness change rate met the index (as shown in Figure 5) was used. The solution was replenished in batches, and other conditions were the same. The cleaning and texturing of the silicon wafers and subsequent process flow were completed, and the efficiency of the battery was measured.
[0041]
[0042] A stable replenishment system was established by using the surface roughness change rate value, resulting in a textured pyramid with a stable surface roughness change rate, and the average efficiency was improved by 0.1%-0.2%.
[0043] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. A method for replenishing electrolyte in a CP tank using the surface roughness change rate of a heterojunction solar cell, characterized in that: Includes the following steps: Step a. Pass multiple batches of silicon wafers through the same cleaning tank and CP tank sequentially. Each batch of silicon wafers includes multiple wafers. Select n wafers and test the surface roughness change rate of the wafers. Calculate the average surface roughness change rate Y' of the n wafers. If the average Y' is within 8-12%, do not replenish the CP tank. If the average Y' is not within 8-12%, replenish the CP tank. The CP solution in the CP tank has a HF concentration of 2-10%, an HCl concentration of 0.5-15%, and an ozone concentration of 30-50 ppm. The method for testing the surface roughness change rate of the silicon wafer includes the following steps: S1. The silicon wafer is texturized in a cleaning tank. The surface of the silicon wafer after texturing forms a pyramidal textured surface. The surface roughness R0 of the pyramidal textured surface is measured using a confocal microscope. S2. Place the texturized silicon wafer in a CP bath containing CP solution. The CP solution rounds the pyramid textured surface. Measure the surface roughness R1 of the rounded pyramid textured surface. The concentration of HF in the CP solution is 2-10%, the concentration of HCl is 0.5-15%, and the concentration of ozone is 30-50 ppm. S3. Calculate the surface roughness change rate Y1 of the pyramid textured surface using the surface roughness change rate formula. The surface roughness change rate value is quantitatively characterized by the percentage reduction in surface roughness relative to the unrounded surface roughness. That is, the surface roughness change rate formula is: Y1=(R0-R1) / R0. S4. Repeat steps S1 to S3 to obtain a series of surface roughness change rates.
2. The method according to claim 1, characterized in that: When the average surface roughness change rate of the silicon wafer is not within 8~12%, reset the liquid replenishment volume of the CP tank to m2, repeat the original test group, keep the test conditions before batch n-1 unchanged, add liquid replenishment volume m2 after batch n-1, and then, according to step a, determine whether the average surface roughness change rate of the silicon wafer obtained by testing and calculation is within 8~12%.
Citation Information
Patent Citations
Surface cleaning and texturing process for crystalline solar cells
CN102017176A
Inorganic composition
JP2007223884A